Sifat Sensori dan Kimia Mochi dengan Substitusi Tepung Kedelai - Sonjaya, Nabila Rizqi Chairiyati; Hapsari, Distya Riski; Rohmayanti, Titi (Jurnal Ilmiah Pangan Halal, 2022)
Mochi is a cake made from white glutinous rice flour, semi-wet, round in shape, high in carbohydrates, low in protein, and Japanese food. The research aims to determine the substitution of soy flour in increasing the nutritional value of sufficient protein for consumption by the public. The study used a completely randomized design using two factors (the first factor was three ratios of white glutinous rice flour and soybean flour 95:5, 90:10, and 85:15. The second factor was the difference in steaming time (10 minutes, 15 minutes, and 20 minutes). Statistical data analysis was used for the organoleptic test using variance (ANOVA) with Duncan’s advanced test at a 95% confidence interval. The selected mochi according to the hedonic results and protein content was treated with 15% soy flour: 85% white glutinous rice flour with steaming time for 20 minutes. The sensory quality test results showed a slight soy taste and chewy texture, a slightly unpleasant smell, the color of the white mochi was slightly yellowish, and the hedonic test had texture, taste, color, aroma, and overall attribute values that were preferred by the finalists. Selected mochi showed 0.91% ash content, 47.38% carbohydrate content, 10.72% protein, 1.1% fat content, and 39.44% water content.